Cyclodextrin‐Confined Supramolecular Lanthanide Photoswitch. Issue 24 (18th May 2022) - Yu, Hua‐Jiang; Wang, Haoran; Shen, Fang‐Fang; Li, Feng‐Qing; Zhang, Ying‐Ming; Xu, Xiufang; Liu, Yu
Abstract: The utilization of azobenzene‐based photoisomerization cannot only control the morphology of supramolecular assemblies, but can also regulate many biological processes. However, the design of azobenzene‐involved nanoconstructs with switchable photoluminescence remains challenging because of the light‐quenching ability of azobenzene. Herein, an azobenzene‐derived multicomponent nanosystem is reported and its function as a supramolecular lanthanide photoswitch is explored. The metal chelation between lanthanide ions (Ln 3+  = Eu 3+ and Tb 3+ ) and 2, 6‐pyridinedicarboxylic acid is utilized as the light‐emitting center but its inherent fluorescence emission is completely suppressed via the disordered motion of the adjoining azophenyl unit. Interestingly, the hydrophobic cavity of α‐cyclodextrin can provide a confined microenvironment to immobilize the molecular conformation of trans ‐azobenzene, thus leading to the recovery of characteristic lanthanide luminescence both in aqueous solution and the hydrogel state. Also, the luminescence can be reversibly turned off when the cis ‐azobenzene is expelled from the cavity of α‐cyclodextrin upon alternating light irradiation. This mutual cooperation arising from host–guest complexation and metal–ligand coordination confers the desired photoswitchable luminescence abilities on the commonly used azobenzenes, which may hold great promise in the creation of more advanced light‐responsive smart materials. Abstract : An azobenzene‐derived supramolecular lanthanide assembly is constructed by the conformational confinement with α‐cyclodextrin, which can exhibit switchable luminescence upon the photoisomeric host–guest complexation by irradiating at different wavelengths.